Some Reflections on Economic Factors in the Political Unification of Nomadic Peoples (Zien Journal of Social Sciences and Humanities, 2022)
In the article, the author spoke about the theoretical issues of the emergence and spread of the first "political associations" in the nomadic peoples of Central Asia, economic factors, their areas of residence and the direction of migration, economy